Hands-on financial modeling with Microsoft Excel 365 : build your own practical models for forecasting, valuation, trading, and growth analysis using Excel 365 /: build your own practical models for forecasting, valuation, trading, and growth analysis using Excel 365. (2022) - Oluwa, Shmuel
No abstract available